Pengaruh Alokasi Dana Desa Terhadap Pemberdayaan dan Peningkatan Kesejahteraan Masyarakat di Desa Padamulya - Husaeni, Rubi Mutiara All; Suantha, Kasan K. (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study focuses on the impact of village fund allocation on the empowerment and improvement of community welfare in Padamulya Village. The research problem raised is how the allocation of village funds affects these two aspects. The methodology used is a quantitative approach with simple linear regression analysis, where data was collected through questionnaires distributed to 100 respondents who are village residents. The results of the study indicate that the allocation of village funds has a positive and significant impact on community empowerment, with a regression coefficient of 1.148 and a significance level of 0.000. Additionally, the allocation of village funds also contributes to the improvement of community welfare, with a regression coefficient of 0.638 and a significance level of 0.000. The conclusion of this study emphasizes that effective management of village funds can enhance community participation and their overall quality of life. Therefore, strategic steps are needed to ensure transparency and accountability in the use of village funds so that the benefits can be optimally felt by the community.